A very simple solvent-free method for the synthesis of 2-arylchromones using KHSO4 as a recyclable catalyst - Pérez, María Emilia (2016)
An efficient and solvent-free procedure for the synthesis of flavones using KHSO4 as a recyclable catalyst is described. The methodology represents an environmentally friendly process in comprehensive consideration compared with other catalytic systems listed in publications. This method provides a clean, simple, solvent-free reaction and useful alternatives to prepare flavones and chromones. The use of KHSO4 catalyst provides excellent yields, also leading to an easy separation and recovery of the catalysts, which allows both low environmental impact and low cost. Other green advantages of the method are the low formation of wastes and the replacement of corrosive, soluble mineral acids.